2015
DOI: 10.1021/acsbiomaterials.5b00294
|View full text |Cite
|
Sign up to set email alerts
|

Nanogel-Mediated RNAi Against Runx2 and Osx Inhibits Osteogenic Differentiation in Constitutively Active BMPR1A Osteoblasts

Abstract: Trauma-induced heterotopic ossification (HO) and fibrodysplasia ossificans progressiva (FOP) are acquired and genetic variants of pathological bone formation occurring in soft tissues. Conventional treatment modalities target the inflammatory processes preceding bone formation. We investigated the development of a prophylaxis for heterotopic bone formation by addressing the biological basis for HO – dysregulation in the bone morphogenetic protein (BMP) signaling pathway. We previously reported the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Our study demonstrated that knocking down miR-146a significantly promoted SMAD4 expression, this might greatly enhance the transcriptional activity of the SMAD protein complex and subsequently lead to an amplified cascade of expression of downstream osteogenic specific genes, making ADSCs more “sensitive” to commit osteogenesis under the induction of surrounding BMP2, which partly explained the improved reparative effects of miR-146a-knockdown ADSCs. Collectively, our data showed preliminary results that miR-146a could either promote or attenuate ADSC-mediated bone formation, which made miR-146a a novel molecular target for specific therapeutic interventions in curing large bone defects, as well as helping the development of new strategies in preventing pathological ectopic bone formation 54 55 56 57 . Although the development of miRNA-based therapeutic strategies opens up new opportunities for the potential clinical application in the future, however, the nature of miRNA-mediated gene regulation still requires further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…Our study demonstrated that knocking down miR-146a significantly promoted SMAD4 expression, this might greatly enhance the transcriptional activity of the SMAD protein complex and subsequently lead to an amplified cascade of expression of downstream osteogenic specific genes, making ADSCs more “sensitive” to commit osteogenesis under the induction of surrounding BMP2, which partly explained the improved reparative effects of miR-146a-knockdown ADSCs. Collectively, our data showed preliminary results that miR-146a could either promote or attenuate ADSC-mediated bone formation, which made miR-146a a novel molecular target for specific therapeutic interventions in curing large bone defects, as well as helping the development of new strategies in preventing pathological ectopic bone formation 54 55 56 57 . Although the development of miRNA-based therapeutic strategies opens up new opportunities for the potential clinical application in the future, however, the nature of miRNA-mediated gene regulation still requires further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…BMSCs from osteoporotic women exhibit a deficient ability to differentiate along the osteogenic linage, as evidenced by low levels of ALP activity and phosphate deposition . Likewise, inhibition of the osteogenic differentiation of BMSCs results in fewer calcified nodules and low expression of specific osteogenic genes and proteins . In contrast, inhibition of adipogenic differentiation and promotion of osteogenic differentiation of BMSCs can alleviate osteoporosis .…”
Section: Discussionmentioning
confidence: 99%
“…We then asked whether BMP signaling is also involved in WWP2-modulated RUNX2 ubiquitination. The constitutively active form of the type 1A BMP receptor, Bmpr1a-CA, was expressed in HEK293T cells to mimic the activation of BMP signaling (44). Indeed, co-expression of Bmpr1a-CA obviously enhanced WWP2-modulated RUNX2 ubiquitination (Fig.…”
Section: The Type 1a Bmp Receptor Potentiates the Wwp2-runx2 Axismentioning
confidence: 99%